2006
DOI: 10.1029/2005jd006454
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evolution of upper stratospheric ozone at selected stations of the Network for the Detection of Stratospheric Change (NDSC)

Abstract: The long‐term evolution of upper stratospheric ozone has been recorded by lidars and microwave radiometers within the ground‐based Network for the Detection of Stratospheric Change (NDSC), and by the space‐borne Solar Backscatter Ultra‐Violet instruments (SBUV), Stratospheric Aerosol and Gas Experiment (SAGE), and Halogen Occultation Experiment (HALOE). Climatological mean differences between these instruments are typically smaller than 5% between 25 and 50 km. Ozone anomaly time series from all instruments, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
91
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 75 publications
24
91
1
1
Order By: Relevance
“…Recent ozone trends calculated for 1997 onwards in this altitude region have shown signs of a small recovery (but not significantly different from a zero trend), although the magnitudes found are typically smaller than those of the chlorine species reported here. Jones et al (2009) reported that ozone is increasing at ∼1.7 % (± ∼ 2.0 % decade −1 ) at mid-latitudes based on linear trends from 1997-2008, while Steinbrecht et al (2006) suggest a 1997-2005 trend for Hawaii to be increasing by 1.9 % ± 1.9 % decade −1 . Both of these examples show trend magnitudes to be less than the trend values estimated here using HCl and ClO.…”
Section: Discussion Of Hcl and Clo Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent ozone trends calculated for 1997 onwards in this altitude region have shown signs of a small recovery (but not significantly different from a zero trend), although the magnitudes found are typically smaller than those of the chlorine species reported here. Jones et al (2009) reported that ozone is increasing at ∼1.7 % (± ∼ 2.0 % decade −1 ) at mid-latitudes based on linear trends from 1997-2008, while Steinbrecht et al (2006) suggest a 1997-2005 trend for Hawaii to be increasing by 1.9 % ± 1.9 % decade −1 . Both of these examples show trend magnitudes to be less than the trend values estimated here using HCl and ClO.…”
Section: Discussion Of Hcl and Clo Resultsmentioning
confidence: 99%
“…By being able to separate the relative contributions of known variation (by the process of linear regression), we will be left with the unexplained variability of the monthly mean signal to which a linear trend can be applied. We follow similar approaches to that of Newchurch et al (2003), and Steinbrecht et al (2004Steinbrecht et al ( , 2006, where we firstly remove the seasonal cycle from the HCl time series. This is simply done for each instrument by finding the difference between each monthly mean value from their corresponding average (climatological) annual cycle.…”
Section: Removing Known Sources Of Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…GROMOS is part of the Network for the Detection of Atmospheric Composition Change (NDACC), and its data set is used for cross-validation of satellite experiments, studies of ozone-climate interactions and middle atmospheric dynamics, as well as for long-term monitoring of the ozone layer in the stratosphere (Peter and Kämpfer, 1995;Peter et al, 1996;Calisesi et al, 2001;Dumitru et al, 2006;Hocke et al, 2006;Steinbrecht et al, 2006;Hocke et al, 2007;Flury et al, 2009;Steinbrecht et al, 2009;Studer et al, 2012;Hocke et al, 2013).…”
Section: Gromos Radiometermentioning
confidence: 99%